2010
DOI: 10.1530/eje-10-0090
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, androgen receptor gene CAG repeat length, mood and behaviour in adolescent males

Abstract: Objectives: Androgen activity has been implicated in a range of traits and behaviours that have well-documented sex differences. However, the results of the studies on the relationship between testosterone and these traits and behaviours are inconsistent. This study has analyzed i) whether CAG repeat length, a presumed modulator of androgen receptor sensitivity, is associated with sex-dimorphic traits and behaviours (aggressive and non-aggressive risk-taking (ART and NART), dominance, depressive symptoms and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 48 publications
3
50
0
Order By: Relevance
“…It is proposed that longer CAG repeat length causes lower transcriptional activity of genes activated by testosterone binding (43). A longer (>23) and a shorter (≤20) than average amount of CAG triplets have been suggested as risk alleles (44). Longer CAG repeat length is associated with more depressive symptoms (45).…”
Section: Genetic Risk Constellationmentioning
confidence: 99%
“…It is proposed that longer CAG repeat length causes lower transcriptional activity of genes activated by testosterone binding (43). A longer (>23) and a shorter (≤20) than average amount of CAG triplets have been suggested as risk alleles (44). Longer CAG repeat length is associated with more depressive symptoms (45).…”
Section: Genetic Risk Constellationmentioning
confidence: 99%
“…A CAG repeat polymorphism within the AR gene was found to influence the transactivation of androgendependent genes (17,18). The length of the CAG repeats varies between w12 and 30 repeats with an average length of 22 in Caucasian populations (19)(20)(21)). An inverse relationship exists between AR CAG repeat length and the transcriptional activity of testosterone target genes (18).…”
Section: Introductionmentioning
confidence: 99%
“…10,11,14,21,22 Previous studies have identified a relationship between a smaller number of CAG repeats and increased impulsivity in males. 2124 Impulsivity has also been associated with an increased risk of developing alcoholism in males and increased alcoholism severity, but a paucity of data exists regarding females. 11,12 To our knowledge, there are no reports examining the influence of the CAG repeat length of the AR gene on psychiatric outcomes in females.…”
Section: Discussionmentioning
confidence: 99%
“…The length of the polyglutamine tract and impulsivity have been inversely related in males, 21,24 but to our knowledge, no data are available describing the relationship between the size of the AR allele and impulsivity or the AR CAG repeat length and alcoholism in females. We sought to provide additional insight into the correlation between CAG repeat length of the AR gene and alcoholism by comparing the repeat lengths with measures of alcoholism and psychiatric severity, in a cohort of well-characterized African–American and Caucasian alcoholic females.…”
Section: Introductionmentioning
confidence: 98%